2011
DOI: 10.1016/j.cub.2011.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Phytochrome Regulation of Cellulose Synthesis in Arabidopsis

Abstract: Plant development is highly plastic and dependent on light quantity and quality monitored by specific photoreceptors. Although we have a detailed knowledge of light signaling pathways, little is known about downstream targets involved in growth control. Cell size and shape are in part controlled by cellulose microfibrils extruded from large cellulose synthase complexes (CSCs) that migrate in the plasma membrane along cortical microtubules. Here we show a role for the red/far-red light photoreceptor PHYTOCHROME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
109
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(118 citation statements)
references
References 19 publications
(29 reference statements)
5
109
4
Order By: Relevance
“…Stomatal pore dimensions, guard cell pair dimensions, and guard cell dimensions in wild-type and xxt1 xxt2 plants during FC or ABA treatment Stomatal aperture, stomatal pore length, ratio of aperture to pore length, guard cell pair height, guard cell pair width, aspect ratio of guard cell pairs (height to width), ratio of aperture to guard cell pair width, guard cell diameter, and guard cell length were measured on a single stomate basis using epidermal peels from 3-to 4-week-old plants. suggesting that cellulose biosynthesis might be a downstream target of phytochrome B-involved light signaling pathways in cesa6 prc1-1 hypocotyls (Bischoff et al, 2011). The discrepancy in the effect of darkness on CSC motility between our results in guard cells and the previous results in cesa6 prc1-1 hypocotyls (Bischoff et al, 2011) could be attributed to the tissue specificity of dark-responsive signaling or different durations of dark treatment.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Stomatal pore dimensions, guard cell pair dimensions, and guard cell dimensions in wild-type and xxt1 xxt2 plants during FC or ABA treatment Stomatal aperture, stomatal pore length, ratio of aperture to pore length, guard cell pair height, guard cell pair width, aspect ratio of guard cell pairs (height to width), ratio of aperture to guard cell pair width, guard cell diameter, and guard cell length were measured on a single stomate basis using epidermal peels from 3-to 4-week-old plants. suggesting that cellulose biosynthesis might be a downstream target of phytochrome B-involved light signaling pathways in cesa6 prc1-1 hypocotyls (Bischoff et al, 2011). The discrepancy in the effect of darkness on CSC motility between our results in guard cells and the previous results in cesa6 prc1-1 hypocotyls (Bischoff et al, 2011) could be attributed to the tissue specificity of dark-responsive signaling or different durations of dark treatment.…”
Section: Discussioncontrasting
confidence: 56%
“…suggesting that cellulose biosynthesis might be a downstream target of phytochrome B-involved light signaling pathways in cesa6 prc1-1 hypocotyls (Bischoff et al, 2011). The discrepancy in the effect of darkness on CSC motility between our results in guard cells and the previous results in cesa6 prc1-1 hypocotyls (Bischoff et al, 2011) could be attributed to the tissue specificity of dark-responsive signaling or different durations of dark treatment. We speculate that the increase in GFP-CESA3 speed in guard cells bordering closed stomata and in neighboring pavement cells, in light of the findings from previous studies (Bischoff et al, 2011;Boex-Fontvieille et al, 2014), might be attributed, at least in part, to posttranslational modulation of CESA3 CSCs migrate at the plasma membrane in linear trajectories coaligned with underlying cortical MTs, the presence of which is not a strict requirement for CSC motility (Paredez et al, 2006;Chen et al, 2010).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The effect that genetic mutations have on cellulose polymerization rates can therefore be explored by examining the displacement velocity of fluorescently labeled CESA at the PM. Although previous analyses of the CESA velocity in cellulose deficient or MT mutants have suggested that polymerization rate can be altered, these studies have not addressed the influence that microfibril structure could impart on CESA velocity (21)(22)(23)(24).…”
mentioning
confidence: 99%
“…Phosphorylation of CESA5 modulates migration of CESA complexes containing the CESA6-related isoform, CESA5, which is coordinated by phytochrome activation (Bischoff et al, 2011). Therefore, it was of interest to examine if and how phosphorylation of CESA3 regulates interactions of CESA particles with cortical microtubules, particularly microtubule-guided bidirectional synthesis and deposition of cellulose microfibrils.…”
mentioning
confidence: 99%